A reactive force field for aqueous-calcium carbonate systems - Gale, Julian; Raiteri, Paolo; van Duin, A. (Royal Society of Chemistry, 2011)
A new reactive force field has been derived that allows the modelling of speciation in the aqueous-calcium carbonate system. Using the ReaxFF methodology, which has now been implemented in the program GULP, calcium has been simulated as a fixed charge di-cation species in both crystalline phases, such as calcite and aragonite, as well as in the solution phase. Excluding calcium from the charge equilibration process appears to have no adverse effects for the simulation of species relevant to the aqueous environment. Based on this model, the speciation of carbonic acid, bicarbonate and carbonate have been examined in microsolvated conditions, as well as bulk water. When immersed in a droplet of 98 water molecules and two hydronium ions, the carbonate ion is rapidly converted to bicarbonate, and ultimately carbonic acid, which is formed as the metastable cis-trans isomer under kinetic control. Both first principles and ReaxFF calculations exhibit the same behaviour, but the longer timescale accessible to the latter allows the diffusion of the carbonic acid to the surface of the water to be observed, where it is more stable at the interface. Calcium carbonate is also examined as ion pairs in solution for both CaCO30(aq) and CaHCO3+(aq), in addition to the (104) surface in contact with water.